O ensino do direito educacional no contexto da pandemia de COVID-19 - Oliveira, Isabela Fadul de (2021)
This article aims to discuss an educational experience in the context of pandemic COVID-19. More specifically, it is intended to present the pedagogical strategies adopted to carry out the Educational Law discipline during the Supplementary Academic Semester of the Federal University of Bahia, in order to reflect on the challenges of remote in legal courses during 2020, especially in what it concerns the transformations produced in the transition from face-to-face teaching to remote teaching. The text discusses three dimensions of the experience, namely: the adaptation of the roles of teachers and students in remote education, accessibility to sources for teaching and learning law, and innovations in the forms of learning assessment, with special attention to the logbook. For that, the study makes use of institutional documents, administrative records, questionnaires, student evaluation and monitoring reports and teaching internship. At the end, the text points to the possibilities of incorporating the experiences lived in the context of resuming classroom teaching in legal courses